PWE-400 The effect of periodic feedback on screening colonoscopy for colorectal polyp and adenoma detection rate in gastroenterology fellow. (22nd June 2015) - Jin, EH; Im, JP; Seo, JY; Kim, JS
Abstract : Introduction: Adenoma detection rate is important quality indicator in screening colonoscopy. The aim of this study was to measure the change in the colorectal polyp and adenoma detection rate before and after monitoring and feedback in first-year gastroenterology fellow. Method: We prospectively analysed a total of 3312 screening colonoscopy data including successful cecal intubation rate, cecal intubation time, withdrawal time, polyp and adenoma detection at the Seoul National University Hospital between March 2013 and September 2014. 1959 colonoscopies performed by 7 first-year gastroenterology fellows without feedback (group A). And 1353 screening colonoscopies performed by another 6 first-year fellows who were informed the periodic monitoring and feedback (group B). We sent the results of polyp and adenoma detection rate to all fellows and professor in charge every month by E-mail. Then we compared before and after feedback group outcomes. Results: The average age of patients was 59.4 years, and 55.8% were male. The successful cecal intubation rate was improved after 150 cases both group A (90.0%) and group B (91.3%). Before feedback, overall polyp detection rate was 0.51 ± 0.08, adenoma detection rate was 0.36 ± 0.05. After feedback, the overall polyp detection rate was 0.50 ± 0.05, adenoma detection rate was 0.36 ± 0.03. Compared with before and after feedback group, there was not a significant difference in overall polyp and adenoma detection rate (p = 0.901, p = 0.846). After 150 cases, polyp detection rate was 0.50 for group A, whereas 0.56 for group B (p = 0.041). And adenoma detection rate was significantly higher in group A than group B (0.37 vs. 0.42; p = 0.038). Conclusion: The minimum threshold number of technical competence in colonoscopy is more than 150 colonoscopies for trainee who initially started learning colonoscopy. The monitoring and feedback program is associated with an increase in polyp and adenoma detection rate after 150 cases. The periodic monitoring and feedback can be effective for trainees who achieved technical competence. Disclosure of interest: None Declared.